A Versatile Scanning Photocurrent Mapping System to Characterize Optoelectronic Devices based on 2D Materials. Issue 7 (29th May 2017) - Reuter, Christoph; Frisenda, Riccardo; Lin, Der‐Yuh; Ko, Tsung‐Shine; Perez de Lara, David; Castellanos‐Gomez, Andres
Abstract : The investigation of optoelectronic devices based on 2D materials and their heterostructures is a very active area of investigation with both fundamental and applied aspects involved. Here, a description of a home‐built scanning photocurrent microscope is presented, which is designed and developed to perform electronic transport and optical measurements of 2D‐materials‐based devices. The complete system is rather inexpensive (<10 000 €) and it can be easily replicated in any laboratory. To illustrate the setup, current–voltage characteristics are measured, in the dark and under global illumination, of an ultrathin p–n junction formed by the stacking of an n‐doped few‐layer MoS2 flake onto a p‐type MoS2 flake. Scanning photocurrent maps are then acquired, and by mapping the short‐circuit current generated in the device under local illumination, it is found that at zero bias, the photocurrent is generated mostly in the region of overlap between the n‐type and p‐type flakes. Abstract : Optoelectronics devices based on 2D materials, such as p–n junctions or Schottky photodiodes, are generating large interest thanks to their reduced dimensions combined with outstanding performances. A fast and inexpensive scanning photocurrent setup that is able to resolve spatially the generation of photocurrent in these devices is discussed.